2016
DOI: 10.2174/1567205013666151116125518
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Regenerative Capacity of Oligodendrocyte Progenitor Cells (NG2-Glia) in the Ageing Brain: A Vicious Cycle of Synaptic Dysfunction, Myelin Loss and Neuronal Disruption?

Abstract: Oligodendrocytes are specialised glial cells that myelinate CNS axons. Myelinated axons are bundled together into white matter tracts that interconnect grey matter areas of the brain and are essential for rapid, integrated neuronal communication and cognitive function. Life-long generation of oligodendrocytes is required for myelination of new neuronal connections and repair of myelin lost through natural 'wear and tear'. This is the function of a substantial population of adult oligodendrocyte progenitors (OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…However, in WM diseases like multiple sclerosis and VaD, remyelination failure during disease progression eventually occurs due to impaired survival, proliferation, migration, recruitment, and differentiation of OPCs (Maki, et al, 2013). In the aging brain, there is white matter shrinkage and decreased myelination, which is exacerbated and accelerated in dementia, suggesting a decline in the regenerative capacity of OPCs (Rivera, et al, 2016). Our data show that MMI in RB rats significantly decreased the number of OPCs in the corpus callosum and striatum.…”
Section: Discussionmentioning
confidence: 99%
“…However, in WM diseases like multiple sclerosis and VaD, remyelination failure during disease progression eventually occurs due to impaired survival, proliferation, migration, recruitment, and differentiation of OPCs (Maki, et al, 2013). In the aging brain, there is white matter shrinkage and decreased myelination, which is exacerbated and accelerated in dementia, suggesting a decline in the regenerative capacity of OPCs (Rivera, et al, 2016). Our data show that MMI in RB rats significantly decreased the number of OPCs in the corpus callosum and striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ischemia induces white matter injury, and subsequently the young adult brain mounts and endogenous effort to stimulate proliferation of OPCs and migration towards demyelinated areas in order to differentiate into mature oligodendrocytes and restore myelin sheaths. Others have suggested that the capacity for the repair of white matter injury diminishes with increased age [ 48 , 73 , 74 ]. Our previous studies demonstrate that n-3 PUFAs preserve the integrity of white matter and enhance oligodendrogenesis in young adult mice following ischemic insults [ 23 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to differentiating into mature myelinating oligodendrocytes, OPCs transition through an intermediate phase identified by expression of the G-protein coupled receptor GPR17 (Viganò et al, 2016). Notably, early changes in OPCs may be a pathological sign and underlie myelin loss in mouse models of AD-like pathology (Rivera et al, 2016, Vanzulli et al, 2020. This possibility is supported by immunostaining of post-mortem AD brain showing reduced NG2 immunoreactivity in individuals with high A plaque load (Nielsen et al, 2013b).…”
Section: Introductionmentioning
confidence: 96%